Governing Metropolitan Transport : Institutional Solutions for Policy Problems - Busetti, Simone (SpringerBriefs in Applied Sciences and Technology,, 2015)
This book investigates the link between institutions and public policies with specific reference to transport. It opens by examining the main arguments for the establishment of metropolitan transport authorities. The potential impacts of institutional change on the policy efficiency of institutions are then examined. Key problems for institutional designers are identified, showing how they can hamper the achievement of desired policy outcomes through institutional solutions. Two in-depth case studies on institutional change in metropolitan transport (in London and Barcelona) are presented with a view to testing the aforementioned hypotheses and providing insights into the ways in which the two transport institutions were reformed. The concluding chapter identifies lessons for institutional designers and highlights the policy results that may be expected from the constitution of metropolitan transport authorities.